LFG-500, a novel synthetic flavonoid, suppresses epithelial–mesenchymal transition in human lung adenocarcinoma cells by inhibiting NLRP3 in inflammatory microenvironment. (1st August 2017) - Yang, Dan; Cao, Xin; Wang, Fan; Jiang, Haijing; Feng, Dingding; Guo, Hao; Du, Lei; Jin, Yingliang; Chen, Yansu; Yin, Xiaoxing; Li, Chenglin
Abstract: Increasing evidence indicates that inflammatory microenvironment facilitates tumor metastasis. Here, we found that LFG-500, a novel synthetic flavonoid, significantly inhibited epithelial–mesenchymal transition (EMT) in human lung adenocarcinoma A549 and H1299 cells co-cultured with LPS-challenged THP-1 cells or cultured in THP-1 cell-derived conditioned medium. Moreover, we found that TNF-α is a direct and decisive factor for promoting EMT and LFG-500 suppressed TNF-α-induced EMT and cell motility. NLRP3 knockdown inactivated NLRP3 inflammasome, which subsequently inhibited EMT and blocked cell migration, indicating that TNF-α-induced EMT requires the NLRP3 inflammasome. LFG-500 inhibited the activation of the NLRP3 inflammasome, thus inhibiting EMT. Moreover, LFG-500 treatment significantly inhibited metastasis in vivo by downregulating NLRP3 expression. Importantly, we found that NLRP3 was highly expressed in high-grade lung adenocarcinoma and that its expression was correlated with lymph node metastasis. NLRP3 and vimentin levels were significantly increased in matched metastatic lymph nodes. Moreover, a significant positive correlation was observed between their levels. Together, these results suggest that LFG-500 markedly suppresses EMT by inhibiting the NLRP3 inflammasome in the inflammatory microenvironment and that NLRP3 is a potential biomarker of lung adenocarcinoma metastasis. Highlights: LFG-500 inhibits EMT in lung adenocarcinoma cells in inflammatory microenvironment. TNF-α is found as a direct and decisive factor for promoting EMT. NLRP3 is proved to be required for TNF-α-induced EMT in lung adenocarcinoma cells. Mechanism study reveals LFG-500 can inhibit EMT via repressing NLRP3 inflammasome. NLRP3 is a potential biomarker of lung adenocarcinoma progression and metastasis.